(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The digital age has brought significant changes to how businesses operate, communicate, and innovate. At the core of these transformations is the integration of Artificial Intelligence (AI), which has revolutionized industries, enhanced efficiency, and created new opportunities. Leadership in the digital age requires new strategies, skills, and capabilities to navigate the complexities of this evolving landscape. This paper explores the role of AI in transforming leadership practices, discussing how AI is reshaping leadership models, improving decision-making, fostering innovation, and enhancing employee engagement. Additionally, the paper examines the challenges that leaders face in adopting AI and the ethical considerations they must navigate. Through a comprehensive review of current literature, case studies, and expert opinions, the paper provides insights into how leaders can leverage AI to drive organizational success in the digital age.